CO[sub 2] Laser Ablation Area Scaling And Redeposition On Flat Polyoxymethylene Targets - Sinko, John E.; Scharring, Stefan; Eckel, Hans-Albert; Tsukiyama, Yosuke; Umehara, Noritsugu; Ichihashi, Katsuhiro; Ogita, Naoya; Sasoh, Akihiro; Roeser, Hans-Peter (AIP Conference Proceedings, 2010)
One of the remaining unknown subjects of laser propulsion involves whether special benefits or challenges exist for applying laser ablation propulsion to targets with particularly large or small spot areas. This subject is of high importance for a wide range of topics ranging from laser removal of space debris to micropropulsion for laser propulsion vehicles. Analysis is complex since different ablation phenomena are dominant between atmosphere and vacuum conditions. Progress has also been impeded by the difficulty of setting control parameters (particularly fluence) constant while the spot area is adjusted. It is also usually difficult for one group to address small- and large-area effects using a single high-power laser system. Recent collaborative experiments on laser ablation area scaling at several institutions, using 100-J class and 10-J class COsub 2 lasers, have advanced the understanding of laser propulsion area scaling. The spot area-dependence of laser propulsion parameters has been investigated over an area range covering approximately 0.05-50 cmsup 2 at low fluence of about 0.6 J/cmsup 2. The experiments were conducted well below the threshold for plasma formation, and provide an estimate of the ablation threshold for COsub 2 laser ablation of POM.